EFIKASI DIRI BERKORELASI DENGAN ACTIVITY OF DAILY LIVING (ADL) PADA PASIEN POST OPERASI SECTIO CAESAREA - Suwardi Husni; Rahmi Muslinda; Isneini Isneini; Zulkifli Zulkifli; Saiful Oetama (Poltekkes Kemenkes Aceh, 2023)
Sectio Caesarea is the process of surgery giving birth to the fetus through an incision in the abdominal wall and uterus. This study aims to find out the relationship between self -efficacy of the Activity of Daily Living (ADL) in Post Sectio Caesarea patients in the Mother and Child Hospital. This study uses this instrument The General Self-Efficacy Scale (GSE) questionnaire and the Katz of the Research Index are quantitative research with the correlation method. By using purposivesampling techniques in the population of 36 people. This research was carried out on 15-31 March 2023. Statistic Chi-Square shows that of 36 post operating mothers sectio caesarea, 29 people (80.6%) are young adults (20-35 years), 35 people (97.2%) are Acehnese tribes, 24 people (66, 7%) Educated high school/vocational school and 23 people (63.9%) are housewives (IRT), the highest distribution is in the category of moderate self -efficacy, namely 26 people or as many as (72.2%), and the highest distribution is in the catergori while 19 people or as many as (52.8%). Based on the results of the hypothesis test, it is known that the p-value value is 0.005 <0.05, so that Ho is rejected and the HA is received which is significantly a significant relationship between self-efficacy and the Activity of Daily Living in post-Caesarean section operations. So it is important to have high self -efficacy, the level of confidence in the post operation of SC will be able to complete the Activity of Daily Living (ADL) Increased self -efficacy can be done by providing motivation and spreading leafleat in the hospital.